Legius syndrome in fourteen families - Denayer, Ellen; Chmara, Magdalena; Brems, Hilde; Kievit, Anneke Maat; van Bever, Yolande; Van den Ouweland, Ans MW; Van Minkelen, Rick; de Goede-Bolder, Arja; Oostenbrink, Rianne; Lakeman, Phillis; Beert, Eline; Ishizaki, Takuma; et al. (Human mutation, 2011)
Legius syndrome presents as an autosomal dominant condition characterized by café‐au‐lait macules with or without freckling and sometimes a Noonan‐like appearance and/or learning difficulties. It is caused by germline loss‐of‐function SPRED1 mutations and is a member of the RAS‐MAPK pathway syndromes. Most mutations result in a truncated protein and only a few inactivating missense mutations have been reported. Since only a limited number of patients has been reported up until now, the full clinical and mutational spectrum is still unknown. We report mutation data and clinical details in fourteen new families with Legius syndrome. Six novel germline mutations are described. The Trp31Cys mutation is a new pathogenic SPRED1 missense mutation. Clinical details in the 14 families confirmed the absence of neurofibromas, and Lisch nodules, and the absence of a high prevalence of central nervous system tumors. We report white matter T2 hyperintensities on brain MRI scans in 2 patients and a potential association between postaxial polydactyly and Legius syndrome. © 2010 Wiley‐Liss, Inc.